Pengaruh Online Customer Review dan Harga terhadap Keputusan Menginap di Fahira Hotel Syariah Bukittinggi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of Online Customer Review (OCR) and Price on the decision to stay at Fahira Hotel Syariah Bukittinggi. The background of this study is based on the fluctuation in the number of guests staying, higher room prices compared to similar hotels, and negative reviews from guests regarding hotel cleanliness and facilities. This phenomenon raises questions about the extent to which OCR and price play a role in influencing consumer decisions. This study uses a quantitative correlational method with a purposive sampling technique to 99 respondents who have stayed at Fahira Hotel Syariah Bukittinggi. Data were obtained through distributing questionnaires processed using multiple linear regression analysis with the help of SPSS 24 software. The results of the partial test show that OCR has a positive and significant effect on the decision to stay with a calculated t-value of 2.142> t-table 1.98472 and sig 0.035 <0.05. The price variable also has a positive and significant effect with a calculated t-value of 5.818> t-table 1.98472 and sig 0.000 <0.05. A simultaneous F-test showed that OCR and price significantly influenced the decision to stay, with an F-count of 18.174 > F-table of 3.092 and a significance level of 0.000 < 0.05. The coefficient of determination of 0.615 indicates that 61.5% of the variation in the decision to stay was influenced by OCR and price, while the remaining 38.5% was influenced by other factors. This study provides implications for hotel management to pay more attention to service quality and price adjustments to increase customer satisfaction and interest.